2017
DOI: 10.1038/s41598-017-10329-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Immune Responses During Hepatitis C Virus Infection in Tupaia belangeri

Abstract: Hepatitis C virus (HCV) is a leading cause of chronic liver disease, cirrhosis, and hepatocellular carcinoma. To address the molecular basis of HCV pathogenesis using tupaias (Tupaia belangeri), we characterized host responses upon HCV infection. Adult tupaias were infected with HCV genotypes 1a, 1b, 2a, or 4a. Viral RNA, alanine aminotransferase, anti-HCV core and anti-nonstructural protein NS3 antibody titres, reactive oxygen species (ROS), and anti-3β-hydroxysterol-Δ24reductase (DHCR24) antibody levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 52 publications
(57 reference statements)
2
20
0
1
Order By: Relevance
“…In the same study, we also characterized TLR mRNA expression, and similar to studies in humans, we found increased intrahepatic levels of TLRs 3, 7, and 8 [19]. Remarkably, HCV infection in Tupaia triggered ROS generation in sera and liver tissues and subsequently induced anti-3β-hydroxysterol-∆24-reductase (DHCR24) antibody production [19], similar to observations in human infections [51][52][53][54][55]. A previous study demonstrated anti-DHCR24 auto-antibodies as a biomarker for Hepatitis C progression [56] and the findings of HCV chronic infection in Tupaia also supported the possibility of using anti-DHCR24 antibodies as a valuable marker to monitor HCV infection in vivo.…”
Section: Hepatitis C Virus (Hcv)supporting
confidence: 79%
See 4 more Smart Citations
“…In the same study, we also characterized TLR mRNA expression, and similar to studies in humans, we found increased intrahepatic levels of TLRs 3, 7, and 8 [19]. Remarkably, HCV infection in Tupaia triggered ROS generation in sera and liver tissues and subsequently induced anti-3β-hydroxysterol-∆24-reductase (DHCR24) antibody production [19], similar to observations in human infections [51][52][53][54][55]. A previous study demonstrated anti-DHCR24 auto-antibodies as a biomarker for Hepatitis C progression [56] and the findings of HCV chronic infection in Tupaia also supported the possibility of using anti-DHCR24 antibodies as a valuable marker to monitor HCV infection in vivo.…”
Section: Hepatitis C Virus (Hcv)supporting
confidence: 79%
“…Several studies have demonstrated the susceptibility of Tupaia to infections with different HCV strains, where the disease course of chronic HCV infection was comparable to that observed in humans. However, sustained/intermittent propagation of HCV with medium/low viral loads were observed in Tupaia, which might be associated with a more restricted replication of HCV in Tupaia compared to humans [17][18][19]. In chronic HCV infection, histopathological findings, including lymphocytic infiltration, disturbance of hepatic cords, and initiation of fibrosis in the liver of HCV-infected Tupaia were observed; these findings were similar to those observed in human patients [19].…”
Section: Hepatitis C Virus (Hcv)supporting
confidence: 73%
See 3 more Smart Citations